Gambaran Pelaksanaan Latihan Post Operasi Pada Pasien Bedah Umum Di RS.Pku Muhammadiyah Surakarta - SALAEH, Aneesa; , Siti Arifah,S.Kp.,M.Kes; , Okti Sri Purwanti, S.Kep, Ns, M.Kep .,Ns SP.Kep. MB (2016)
Recovery is required to the client undergoing anesthesia procedures to restore the function of the body is disrupted. recovery procedure can be done after the surgery is post-operative exercises are performed early ambulation in patients immediately after surgery at the start of getting and sitting beside on the bed until the patient step on the bed, stood up and started learn to walk. The purpose of this study was to overview the implementation of post-surgery for general surgery patients in RS.PKU Muhammadiyah Surakarta. This research is descriptive exploratory study. The sample was 40 patients post operasi general surgery at the Hospital of PKU Muhammadiyah Surakarta. The Data processing techniques is using descriptive techniques. Based on the results of research and discussion, so the conclusions of this study are: the implementation of post-surgery training at the hospital. PKU Muhammadiyah include (1) the breathing exercises performed after 15-30 minutes post-surgery, (2) The exercise when performing effective cough largely implemented, (3) exercise when performing a tilted position largely performed 2-3 hours after surgery, (4 ) The largely of leg exercise performed in 3-4 hours after surgery, and (5) The largely of implemented exercise while doing early ambulation largely after 48 hours following surgery.